Open Globe Injury in a Tertiary Care Hospital - Thapa, Bikram Bahadur; Thapa, Dabal Bahadur; Nath, Har Karan (Journal of Nepalgunj Medical College, 2018)
Introduction: Open Globe Injury (OGI) is a type of mechanical eye injury in which there is a full thickness defect of the outer fibrous coat of eye ball. The Prognosis in the eyes with OGI has improved in these days. 2.4% of blindness in Nepal was due to ocular trauma in 1981. The aim of this study was to describe epidemiological profile, clinical profile and treatment outcome in eyes with open globe injury. Methodology: It is the prospective interventional non randomized hospital based study on the patients of open globe injury presented to the Nepalgunj Medical College, Nepalgunj from April 2017 to May 2018. Visual acuity, anterior and posterior segment evaluation, site and size of wound were recorded. All the eyes were underwent primary repair surgery. Postoperative visual acuity, anterior and posterior segment evaluation was carried out on all follow up. Second surgery was done if required. Results: 0.4% of ophthalmic and 0.016% of all hospital patients had open globe injury. Most of the victims were young males. The mean age of study population was 10.98±17.1 year. Playing (62.5%) was the most common time of injury and wooden stick (50%) was most common agent of injury. Zone I involvement (87.5%) and penetrating type (91.7%) was found in most of cases. 87.5% of eyes were blind, 4.2%were visually impaired and 8.3% had normal vision at the time of presentation. 79.2 % of eye were improved after treatment on visual function, 12.5% remained unchanged while 8.3% deteriorates and leads to pthysis bulbi. Conclusion: The incidence of open globe injury was 0.4% among ophthalmic patients and 0.016% among all patients of Nepalgunj Medical College Teaching Hospital, Nepalgunj. Early Primary repair, use of systemic antibiotics and postoperative care provides encouraging anatomical and functional outcome in these eyes with OGI.